The effectiveness of the cognitive restructuring counseling model to help students think academically critical - Yenti Arsini; Yuzarion Yuzarion; Deliati Deliati; Afwan Syahril Manurung (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
Academic critical thinking is a crucial competence for university students; however, many still face difficulties in analytical reasoning, evaluative judgment, and reflective thinking due to irrational beliefs and affective barriers. This study aimed to develop and test the effectiveness of a cognitive restructuring counseling model to enhance students’ academic critical thinking. The study employed a research and development approach with mixed methods, involving n = 30 students, and utilized a quasi-experimental one-group pretest–posttest design. The model was validated by experts, yielding a high feasibility score (M = 4.36; 87.2%). Statistical analysis using a paired-sample t-test revealed a significant improvement in academic critical thinking scores from pretest (M = 61.36) to posttest (M = 80.46), t(29) = XX.XX, p < .05, with a large effect size (Cohen’s d = 1.10). The greatest improvement was observed in metacognitive reflection. These findings indicate that the model effectively promotes rational, reflective, and open thinking patterns by addressing cognitive distortions and affective barriers. The novelty of this study lies in integrating cognitive restructuring counseling with academic critical thinking development within a structured and validated framework, particularly in the context of Islamic higher education.